Transcriptomics-based analysis of genes related to lead stress and their expression in the roots of Pogonatherum crinitum - Zhu, Chenlu; Yu, Junbao; Cao, Shuyi; Wu, Xinyi; Meng, Weicai; Hou, Xiaolong (Frontiers in Plant Science, 2022)
Revealing plants' tolerance and transport genes to heavy metal stress play an important role in exploring the potential of phytoremediation. Taking the heavy metal lead (Pb) hyperaccumulator plant Pogonatherum crinitum (Thunb.) Kunth as the research object, a hydroponic simulation stress experiment was set up to determine the physiological indicators such as antioxidant enzymes and non-enzymatic antioxidants in the roots of P. crinitum under different Pb concentrations (0, 300, 500, 1000, 2000 mg·L-1). RNA-Seq was performed, the Unigenes obtained by transcriptome sequencing were enriched and annotated by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, and the differential expression genes (DEGs) of root were screened and verified by quantitative real-time polymerase chain reaction (qRT-PCR). The results are as follows: with the increase of Pb concentration, superoxide dismutase (SOD), catalase (CAT), and ascorbic acid (AsA) content increased. Peroxidase (POD), malondialdehyde (MDA), and ascorbic acid–glutathione (AsA-GSH) cycles showed low promotion with high inhibition. A total of 38.21 Gb of bases were obtained by transcriptome sequencing, and the base quality of each sample reached Q20 and Q30, accounting for 90%, making the sequencing results reliable. Combined with transcriptome sequencing, functional annotation, and qRT-PCR validation results, 17 root Pb-tolerant genes of P. crinitum were screened out, which were related to antioxidation, transportation, and transcription functions. Moreover, qRT-PCR verification results under different Pb stress concentrations were consistent with the transcriptome sequencing results and changes in physiological indicators. In brief, the root of P. crinitum can adapt to the Pb stress environment by up-regulating the expression of related genes to regulate the physiological characteristics.